IMPLEMENTASI METODE PEMBELAJARAN SNOWBALL THROWING DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR EKONOMI SISWA KELAS XII IPS - Anisaurrohmah Anisaurrohmah; Nurul Hilaliyah; Istri Sakti Andayani (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This study aims to increase the activity and learning outcomes of economics class XII IPS Madrasah Aliyah Negeri (MAN) Insan Cendekia Tanah Laut through the use of the Snowball Throwing learning method in economic subjects for the 2018/2019 academic year. This research is a Classroom Action Research (CAR) which was conducted in two cycles. The first cycle consisted of two meetings and the second cycle consisted of one meeting. Each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The subjects in this study were students of class XII IPS, totaling 22 students. The success indicator in this study is if 75% of students are actively involved in learning and there is also an increase in learning outcomes in each cycle through the post test and if 75% of students can achieve the Minimum Completeness Criteria (KKM) determined by the school, which is 75. The results showed that with the application of the Snowball Throwing method in class XII IPS, the students' learning activeness scores on each indicator overall increased by 19.17%, from an average of 60% in the first cycle and became 79.17% in the second cycle. The increase in mastery of student learning outcomes increased from the first cycle as much as 74% to 84%. Thus, student learning outcomes have reached the KKM score in cycle II.